2009
DOI: 10.1210/jc.2008-2094
|View full text |Cite
|
Sign up to set email alerts
|

Growth Response, Near-Adult Height, and Patterns of Growth and Puberty in Patients with Noonan Syndrome Treated with Growth Hormone

Abstract: rhGH significantly improved height SDS for children with NS at NAH. Duration of prepubertal rhGH and height SDS at puberty were important contributors to NAH. Because starting age of the patients in this report was 11.6 yr, these data suggest that greater growth optimization is possible with earlier initiation of therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
120
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(141 citation statements)
references
References 24 publications
15
120
2
3
Order By: Relevance
“…Thus Kirk et al, observed a moderate increase in height SDS of 0.8 in 10 patients [22], which is in accordance with a rise of 0.87 in 24 patients reported by Raaijmakers et al, [29]. On the other hand, Osio et al, Noordam et al, and Romano et al, reported better outcomes of GH therapy, with increases in height SDS ranging from 1.3 to 1.7 on a total of 112 patients [26,28,30].…”
Section: Gh Therapy In Nssupporting
confidence: 64%
See 3 more Smart Citations
“…Thus Kirk et al, observed a moderate increase in height SDS of 0.8 in 10 patients [22], which is in accordance with a rise of 0.87 in 24 patients reported by Raaijmakers et al, [29]. On the other hand, Osio et al, Noordam et al, and Romano et al, reported better outcomes of GH therapy, with increases in height SDS ranging from 1.3 to 1.7 on a total of 112 patients [26,28,30].…”
Section: Gh Therapy In Nssupporting
confidence: 64%
“…In addition to cardiac and neoplasic adverse effects, GH therapy could potentially interfere with bone homeostasis and with carbohydrate and lipid metabolism. Supporting this view, 6 cases of scoliosis were reported in a panel of 65 patients under GH therapy [30]. Nevertheless, it is important to consider that scoliosis is not rare in NS.…”
Section: Potential Adverses Effects Of Gh Therapymentioning
confidence: 89%
See 2 more Smart Citations
“…These studies have been focused on cohorts including patients with and without molecularly confirmed diagnosis, different genotypes, various age at enrollment, as well as different replacement therapy protocols. Therefore, the analysis of efficacy of GH treatment has provided contradictory results [Kirk et al, 2001;Osio et al, 2005;Otten and Noordam, 2007;Romano et al, 2009;Lee et al, 2012], and a mean height gain ranging between 0.6 and 2 SDS [Dahlgren, 2009].…”
Section: Discussionmentioning
confidence: 99%